GZO transparent conductive oxide thin films fabricating by DC magnetron sputtering - Pham , Thị Lan Anh; Nguyen, Văn Hiếu; Vu, Thị Hạnh Thu; Dinh, Thái Ngọc Hà (Journal of Technical Education Science, 2015)
Ga-doped ZnO (GZO) films were prepared on glass substrates from GZO target by DC magnetron sputtering at room temperature. The effect of target – substrates distance, sputtering time, and sputtering power on optical and electrical properties of the films was investigated. The results show that GZO films have high crystallinitywith (002) peak orientation, the lowest electrical resistivity of 10-4 Ωcm, average transparency of T > 80% in the visible light region.